Acoustic conditioning of the neonatal incubator compartment: Improvement proposal - Rodríguez-Montaño, Víctor M.; Beira-Jiménez, Juan Luis; Puyana-Romero, Virginia; Cueto-Ancela, José Luis; Hernández-Molina, Ricardo; Fernández-Zacarías, Francisco (Frontiers in Pediatrics, 2022)
The objective of this work focuses on the study of the main sources of noise associated with incubators and the acoustic effects that derive from them. The method that has been established is based on tests carried out under different operating conditions of the incubators. Noise levels are analyzed under different boundary conditions (Neonatal ICU and “Controlled environment rooms”). Under normal operating conditions, the levels inside the incubator are around 56 dB(A), values that exceed the maximum limits recommended by the American Academy of Pediatrics. The scope of this study is to evaluate the existing noise levels in the incubator and analyze possible design improvements. The study was carried out in the hospitals of Cádiz, Huelva and Malaga.